A process for the fabrication of ceramic fibre reinforced titanium aluminide - Horsfall, Ian; Cundy, S. J. (Cranfield University, 1992)
This paper describes initial work on a novel process for the production of titanium aluminide matrix composites reinforced with short alumina fibers. The processing route involves an adaption of existing metal matrix composite (MMC) fabrication technology used to produce hybrid particulate/short fiber composites. A preform is produced which contains alumina fibers and titanium metal powder with a fiber content of around 10% by volume and approximately 50% porosity. This preform is then infiltrated with pure aluminum by a squeeze casting process to produce a fully dense composite of titanium powder and alumina fibers in a metallic aluminum matrix. The composite is then heat treated in a hot isostatic press to react the aluminum and titanium to produce a titanium aluminide matrix.